Community-Based Tourism and Biodiversity Conservation in Kibale and Queen Elizabeth Conservation Areas in Uganda - Katswera, Joseph; Mutekanga, Norah M.; Twesigye, Charles K. (African Journal of Education,Science and Technology (AJEST), 2022)
Community-based tourism promotes biodiversity protection and local community welfare. The Queen Elizabeth and Kibale Conservation Areas in Uganda were investigated. To find out more about the importance of local communities and community-based tourist groups in biodiversity conservation, as well as the issues facing community-based tourism, a household survey was conducted from January to April 2019. This study used semi-structured surveys, focus group discussions, key informant interviews, and remote sensing to obtain primary data. A total of 242 people were surveyed. Data was analysed using various statistical tests, and presented results in tables and figures. Participation of communities in community-based tourism development was motivated by financial and non-financial benefits which encouraged them to participate in conserving biodiversity. They participated through collaborative resource management, and offering tourism programs, products and services to their visitors. Community-based tourism contributed to the overall biodiversity conservation, cultural heritage management, and improvement of people’s welfare. In strengthening community-based tourism, park management provided skills, benefit sharing schemes, ensure compliance of the community-based tourism facilities, and increased conservation education and awareness which further promoted conservation of biodiversity. In conclusion, community-based tourism plays a positive role in promoting wildlife and biodiversity conservation. However, it’s challenged by competition from private tour operators and privately owned hoteliers, inadequate product development and diversification, inadequate access and infrastructure, meeting customer expectations, inadequate knowledge and skills, COVID-19, and security related challenges, among others. Finally, there is need to enhance skills of local communities in community-based tourism development. To market and promote community-based tourism, private sector should strengthen “market intelligence” and also develop a destination branding and marketing strategy.